A Distributed LT Code Design for Multiple-Access Relay Networks Subject to Erasures - Yang, Haitao; Jiang, Ming; Shen, Hong; Zhao, Chunming (IEEE communications letters, 2015)
This letter proposes a new distributed Luby transform (LT) code which is particularly suitable for the multiple-access relay network with erasure channels. We analyze the asymptotic performance of our distributed coding scheme by virtue of AND-OR tree analysis and present the simulation results of finite length comparing with existing methodologies. The proposed coding scheme is shown to be superior to conventional strategies in presence of both source-relay and relay-sink erasures.